2020
DOI: 10.1002/tbio.202000008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bacterial kill in human roots infected with Enterococcus faecalis biofilm following 980 nm laser activation of chlorhexidine

Abstract: Effectiveness of root canal disinfection greatly determines the success of endodontic treatment. The purpose of this study was to evaluate the bacterial killing efficacy of chlorhexidine (CHX) activated with a Gemni 980 nm diode laser. Bacterial kill at the apical one third of the endodontically prepared roots were assessed using the 3D fluorescent microscope (SZX16) after staining the tooth with BacLight SYTO 9 (Live/Dead). The percentage of bacterial kill was calculated by measuring the total amount of green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…In 2020, Jiang et al . evaluated the bacterial eradication efficacy of CHX activated with a laser at the roots’ apical one-third and tested by using a 3D fluorescence microscope, they concluded that a greater number of bacteria were destroyed with laser-assisted irrigation immediately following treatment ( 13 ). This study aimed to investigate if agitating the root canals with an Erbium laser improved the efficiency of 2% CHX against mature E. faecalis biofilm in the lower human molar systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Jiang et al . evaluated the bacterial eradication efficacy of CHX activated with a laser at the roots’ apical one-third and tested by using a 3D fluorescence microscope, they concluded that a greater number of bacteria were destroyed with laser-assisted irrigation immediately following treatment ( 13 ). This study aimed to investigate if agitating the root canals with an Erbium laser improved the efficiency of 2% CHX against mature E. faecalis biofilm in the lower human molar systems.…”
Section: Introductionmentioning
confidence: 99%
“…The most previous work on irrigation activation methods has been done about the improvement of biofilm removal by the laser agitation of chlorhexidine in an infected single root canal with Enterococcus faecalis biofilm obtained after a short incubation period [15,16]. The goal of this study was to examine whether mechanical agitation by Er,Cr:YSGG laser improves the effectiveness of 2% chlorhexidine against 30-day-old E. faecalis biofilm in human mandibular root canal systems, and use of AFM to investigate the impact of different irrigation protocols on the topography of the surface by analyzing isthmus surface properties.…”
Section: Introductionmentioning
confidence: 99%